Revitalisasi Kawasan Wisata Berbasis Lingkungan Di Situ Tunggilis Cileungsi - Malik, Muhammad Akmal Ibnu; Pratama, Ade Rafli; Suherman, Cecep; Feriyanto, Ade; Maulana, Arman; Armawan, Adi; Darmawan, Dedy; Muliyadi, Muliyadi; Harsanto, Molbi Febrio; Kumala, Destiana (Jurnal Pengabdian Masyarakat Madani, 2025)
Situ Tunggilis is a potential tourism area located in Situsari Village, Cileungsi District, Bogor Regency, which faces serious challenges in environmental management and public facility maintenance. The main problems include waste accumulation, deteriorating public infrastructure, and limited community participation in tourism management. This community service program aimed to revitalize Situ Tunggilis tourism area through a Community Development approach that actively engaged local residents in all stages of the program. The method consisted of field observation, group discussions, problem identification, and the implementation of physical activities such as repainting facilities, cleaning the situ’s banks, and constructing a bamboo floating dock. The results showed significant improvements in environmental quality, area aesthetics, and local community involvement. The program also opened opportunities for developing local MSMEs, although its execution was limited by time constraints. This activity serves as an effective initial model for realizing a clean, eco-friendly, and sustainable tourism area.